The Influence of Financial Performance and Company Size on Company Value - Aini, Latifah Nazwa; Sundari, Jurika; Saputri, Tia Nanda; Nuryani, Linda; Marie, Finka Enida (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze and determine the influence of financial performance and company size on the value of listed companies on LQ45 in 2024 on the Indonesia Stock Exchange. The method in this study uses a quantitative method with a sampling technique The purposive sampling used was obtained by obtaining 21 companies with 3 years of observation (63 observations). The data source used in this study is secondary data. Data analysis using panel data regression analysis using Eviews software. The test results show that the financial performance is not affect the company's value. The size of the company has a negative and significant effect on the value of the company.